Cytotoxicity of Goniothalamin on the Human Hepatocellular Carcinoma HEPG2 Cell Line - Obaid Al-Qubaisi, Mothanna Sadiq (2009)
Goniothalamin is a biologically active styrylpyrone derivative isolated from various Goniothalamus sp., belonging to the Annonacae family. This plant extract has been reported to be cytotoxic towards several tumor cell lines such as pancreas carcinoma (PANC-1), gastric carcinoma (HGC-27) and breast carcinoma (MCF-7). The purpose of this study was to examine and characterize the in vitro cytotoxicity effect of goniothalamin on the human hepatocellular carcinoma HepG2 cells and normal liver Chang cells and also to study the morphological and biochemical changes of goniothalamin-treated HepG2 and Chang cells. Goniothalamin (2.3 -150 μM; 24, 48 and 72 hours) treatment to HepG2 and Chang cells resulted in a dose and time dependent inhibition of cell growth as assessed by MTT and LDH assays. The data suggest that goniothalamin selectively inhibits HepG2 cells (IC50 of MTT= 4.6(±0.23) μM; IC50 of LDH= 5.20(±0.01) μM for 72 hours) with less inhibition of growth in Chang cells (IC50 of MTT= 35.0(±0.09) μM; IC50 of LDH= 32.5(± 0.04) μM for 72 hours. The cytotoxic activity of goniothalamin on HepG2 cells was confirmed by Trypan blue dye exclusion assay. Goniothalamin reduced the number of viable cells (non-stained) associated with an increase on the number of non-viable cells (stained) and the Viability Indexes were 52 ± 1.73% for HepG2 cells and 62 ± 4.36% for Chang cells at IC50 after 72 hours. Cells were exposed to goniothalamin at lowest concentration (2.3 μM), IC50 (of MTT results), and highest concentration (150 μM) for 24, 48, or 72 hours and then examined for effects on cell cycle (using the flow cytometry) or proliferation (using the BrdU ELISA assay). The cytotoxic activity of goniothalamin was related to the inhibition of DNA synthesis, as revealed by the reduction of BrdU incorporation. At 72 hours with the lowest goniothalamin concentration of 2.3 μM, the normal liver Chang cells retained 97.6% of control proliferation while the liver cancer HepG2 cells were reduced to 19.8% of control proliferation. Goniothalamin caused the accumulation of hypodiploid apoptotic cells in cell cycle analysis by flow cytometry. Goniothalamin arrested HepG2 and Chang cells in the G2/M phase with different degrees. Light microscopy examination of HepG2 and Chang cells exposed to different concentrations of goniothalamin up to 72 h demonstrated changes in cellular morphology; i.e. cell rounding followed by a loss of adherence with subsequent cell shrinkage and blebbing. In addition, the apoptotic cells were more abundant in goniothalamin-treated HepG2 cells (84 ± 4.58%) for 72 hours than in untreated cell (4 ± 2.65%) upon measurement by TUNEL staining. In view of the toxicity of goniothalamin, the kind of cell death, namely apoptosis or necrosis, was assessed. Therefore, staining with fluorescence labeled annexin V in combination with propidium iodide was performed on HepG2 and Chang cells exposed to goniothalamin. The laser scanning cytometry of propidium iodide and annexin V-stained cells indicated that the growth inhibiting effect of goniothalamin was consistent with a strong induction of apoptosis at late stage. This is because the cellular membrane integrity was lost, so the cells exhibited annexin V- and propidium iodidedouble positive up to 85.87 ± 0.78 and 57.69 ± 1.12 in HepG2 and Chang cells after 24 hours, respectively. In order to confirm apoptotic mechanism in the goniothalamintreated cells, caspase 3 activity upon the same treatment conditions was carried out. The results indicate that caspase 3 activity was significantly elevated early in IC50 treated Chang cells (574% of control) after 24 hours and late in IC50 treated cells after 72 hours in HepG2 cells (879% of control). Our findings suggest a potential mechanism for the strong growth inhibitory effect of goniothalamin on this HepG2 liver cancer cells. However, less sensitivity to normal liver Chang cell line was observed by this compound. An important feature of the cytotoxicity by goniothalamin is that it is mediated through apoptosis.